Individual dorsal morphogen binding sites mediate activation and repression in the Drosophila embryo. - Jiang, J (1992)
The dorsal (dl) morphogen gradient is responsible for initiating the differentiation of the mesoderm, neuroectoderm and dorsal ectoderm in the Drosophila embryo. dl encodes a sequence-specific DNA binding protein that belongs to the Rel family of transcription factors. Previous studies have shown that dl activates the mesoderm determinant twist (twi); here we use a combination of site-directed mutagenesis and P-transformation assays to demonstrate that it also functions as a direct transcriptional repressor of a second target gene, zerknüllt (zen). By exchanging dl binding sites between the promoters we show that activator sites from twi can mediate repression when placed in the context of the zen promoter, and that repressor sites from zen can mediate activation in the context of the twi promoter. This represents the first demonstration that common binding sites for any DNA binding protein can mediate both activation and repression in a developing embryo. Evidence is also presented that the affinities of dl binding sites are important for the efficiency of repression, but are not the sole determinants of the threshold response to the dl gradient.